2016
DOI: 10.1002/2015wr017154
|View full text |Cite
|
Sign up to set email alerts
|

Rapid identification of transience in streambed conductance by inversion of floodwave responses

Abstract: Streambed conductance controls the interaction between surface and groundwater. However, the streambed conductance is often subject to transience. Directly measuring hydraulic properties in a river yields only point values, is time‐consuming and therefore not suited to detect transience of physical properties. Here, we present a method to continuously monitor transience in streambed conductance. Input data are time series of stream stage and near stream hydraulic head. The method is based on the inversion of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 38 publications
(51 reference statements)
0
36
0
Order By: Relevance
“…A repeated application of freeze-cores in streambeds or alluvial plains could help to track the high transience of physical properties that occur in fluvial environments (Gianni et al, 2016;Partington et al, 2017). The 3D representation of soil and the high resolution offered by micrometric resolution X-ray CT allows the simulation of infiltration and recharge dynamics on a pore scale, thus providing valuable, process based information related to hydrogeological applications such as the management of riverine ecosystems or remediation strategies in contaminated sites (Zhang et al, 2016).…”
Section: Applications and Perspective Of The Methodsmentioning
confidence: 99%
“…A repeated application of freeze-cores in streambeds or alluvial plains could help to track the high transience of physical properties that occur in fluvial environments (Gianni et al, 2016;Partington et al, 2017). The 3D representation of soil and the high resolution offered by micrometric resolution X-ray CT allows the simulation of infiltration and recharge dynamics on a pore scale, thus providing valuable, process based information related to hydrogeological applications such as the management of riverine ecosystems or remediation strategies in contaminated sites (Zhang et al, 2016).…”
Section: Applications and Perspective Of The Methodsmentioning
confidence: 99%
“…In a semiinfinite homogeneous isotropic confined aquifer as shown in Figure , on the basis of previous studies (e.g., Gianni et al, ; Ha et al, ; Hall & Moench, ; Singh, ; Singh et al, ), the unit response function of the aquifer system to the river stage fluctuation can be described by the following mathematical model: a2ψδx2=ψδt,0.5emx0,0.5emt0, ψδxx=0=ψδx=0δ()tR, ψδ(),x=t=0, ψδ()x,t=0=0, where δ ( t ) is the Dirac delta function representing the impulse change of the river stage (−), a is the aquifer diffusivity (L 2 /T), and R is the river resistance (L) describing the resistance to flow imparted by the river because of its semipervious riverbed and/or bank and the partial penetration of the river (Gianni et al, ; Singh et al, ). The river resistance R thus corresponds to the distance into the riverbanks where the pressure response from the river stage is immediate (or the same).…”
Section: Theoretical Developmentsmentioning
confidence: 98%
“…Gianni et al . [] presented a new approach that allows the detection of transience in hydraulic conductivity of the streambed based on time series measurements of stream stages and the hydraulic response in the aquifer. At their study site, an increase of one order of magnitude of hydraulic conductivity was observed after floods, as well as during periods where the stream drained the aquifer (as opposed to infiltrating it).…”
Section: Streambed Dynamics In Relation To Hydraulic Propertiesmentioning
confidence: 99%
“…After the flood season, the mean and Reviews of Geophysics 10.1002/2016RG000530 median hydraulic conductivity of the streambed decreased, and its variance increased indicating greater heterogeneity in the grain size distribution of the sediments forming the streambed. Gianni et al [2016] presented a new approach that allows the detection of transience in hydraulic conductivity of the streambed based on time series measurements of stream stages and the hydraulic response in the aquifer. At their study site, an increase of one order of magnitude of hydraulic conductivity was observed after floods, as well as during periods where the stream drained the aquifer (as opposed to infiltrating it).…”
Section: Streambed Dynamics In Relation To Hydraulic Propertiesmentioning
confidence: 99%